Optimasi Desain Metal Gasket Tipis Bentuk New Corrugated Untuk Kebutuhan Tekanan Kerja Rendah Dengan Simulasi Komputer - Permanasari, Avita Ayu; Choiron, Moch. Agus; Purnowidodo, Anindito (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Contact width and leakage had been used as the main parameter to optimize a new corrugated metal gasket for high working pressure. The leakage could be reduced as increasing the contact width. On the other hand, gaskets in piping for low pressure were used into distribution of water in the hotel. In this study, thin metal gasket is optimized by using simulation experiment. The design of experimentation (DOE) Taguchi method is used to analyze the effect of each parameter design and to predict optimal design of thin metal gasket. The L27 orthogonal array is concerned to design the experimental matrix for five factors with three levels. The five factors are thickness (t), pitch (p), over hang (OH), lip height (h), and radius convex (R). The observed value is denoted by using the slope of the curve of relationship between contact width and clamping load. The slope of curve is increased; it will be reduce the clamping load. The optimum design of thin metal gasket based on the results of each observed values is a model with thickness (t) = 0.3 mm, pitch (p) = 4 mm, over hang (OH) = 3 mm, lip height (h) = 0.4 mm, and radius convex (R) = 2.5 mm.Keywords: Contact width, leakage, Taguchi, optimum design